1997
DOI: 10.1590/s0100-879x1997000800007
|View full text |Cite
|
Sign up to set email alerts
|

Chronic imipramine treatment-induced changes in acetylcholinesterase (EC 3.1.1.7) activity in discrete rat brain regions

Abstract: Cholinergic as well as monoaminergic neurotransmission seems to be involved in the etiology of affective disorders. Chronic treatment with imipramine, a classical antidepressant drug, induces adaptive changes in monoaminergic neurotransmission. In order to identify possible changes in cholinergic neurotransmission we measured total, membrane-bound and soluble acetylcholinesterase (Achase) activity in several rat brain regions after chronic imipramine treatment. Changes in Achase activity would indicate alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Other behavioural signs observed in the rabbits, include dry nose and mouth, photosensitivity, frequent urination and disorientation. This observation is in agreement with previous reports of Karolewick et al (1996), Camarini and Benedito (1997) and Ebuehi et al (2004aEbuehi et al ( , 2004b. The intraperitoneal administration of amitriptyline and imipramine increased the body weights of rabbits.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Other behavioural signs observed in the rabbits, include dry nose and mouth, photosensitivity, frequent urination and disorientation. This observation is in agreement with previous reports of Karolewick et al (1996), Camarini and Benedito (1997) and Ebuehi et al (2004aEbuehi et al ( , 2004b. The intraperitoneal administration of amitriptyline and imipramine increased the body weights of rabbits.…”
Section: Discussionsupporting
confidence: 94%
“…Sertraline and clozapine belong to antidepressant and antipsychotic drugs respectively, while imipramine and amitriptyline are tricyclic antidepressants. Biochemical studies on imipramine demonstrated that this drug increased the activity of monoamine neurotransmitters, norepinephrine and serotonin by inhibiting their reuptake into neurons (Barker et al, 1992;Camarini and Benedito, 1997;Cantrell et al, 1999). Sertraline is an oral antidepressant drug of the selective serotonin reuptake type.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Although the exact etiology of CVS is unknown, it could be possible that this area of the brain is activated by the various factors or ''triggers'' of CVS leading to manifestation of the vomiting symptoms. Animal studies show that chronic TCA therapy decreases cholinergic neurotransmission in the medulla, 22 selectively modulates the a-2 adrenoreceptors in the nucleus tractus solitarius and reduces the splanchnic sympathetic nervous system discharge by increasing a-2 adrenoreceptor discharge in the rostral ventral medulla. 23 Thus, TCA agents could have effects in these areas of the central nervous system in humans and modify the brain-gut axis and also autonomic dysfunction, 1,24 a possible underlying mechanism for cycles of CVS.…”
Section: Discussionmentioning
confidence: 99%
“…The controls in each group were intraperitoneally injected with 0.5 ml saline, and the experimental rats were given 0.5 ml imipramine hydrochloride (30 mg/kg body wt./day in subacute treatment; 20 mg/kg body wt./day in chronic treatment). These doses and time of administration are usually employed to carry out studies on the mechanism of the action of imipramine [8,9,10]. The animals received the daily dose in one administration.…”
Section: Animals and Treatmentsmentioning
confidence: 99%